2017
DOI: 10.1002/ar.23587
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplasticity of Supraspinal Structures Associated with Pathological Pain

Abstract: Peripheral nerve and spinal cord injuries, along with other painful syndromes such as fibromyalgia, diabetic neuropathy, chemotherapeutic neuropathy, trigeminal neuralgia, complex regional pain syndrome, and/or irritable bowel syndrome, cause several neuroplasticity changes in the nervous system along its entire axis affecting the different neuronal nuclei. This paper reviews these changes, focusing on the supraspinal structures that are involved in the modulation and processing of pain, including the periaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 213 publications
(229 reference statements)
1
38
0
1
Order By: Relevance
“…Along these lines, we demonstrated that CP patients with high ACC glutamate levels had increased pain symptoms and a trend towards decreased quality of life for especially the emotional functioning domain of the quality of life questionnaire. High ACC glutamate levels might indicate neuronal hyperexcitability, which is considered to be important in chronification of neuropathic pain (Boadas-Vaello et al, 2017). A previous pilot study showed that in CP patients responding to treatment with transcranial magnetic stimulation, the decrease in pain was correlated to changes in glutamate and NAA levels in the brain (Fregni et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Along these lines, we demonstrated that CP patients with high ACC glutamate levels had increased pain symptoms and a trend towards decreased quality of life for especially the emotional functioning domain of the quality of life questionnaire. High ACC glutamate levels might indicate neuronal hyperexcitability, which is considered to be important in chronification of neuropathic pain (Boadas-Vaello et al, 2017). A previous pilot study showed that in CP patients responding to treatment with transcranial magnetic stimulation, the decrease in pain was correlated to changes in glutamate and NAA levels in the brain (Fregni et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that proinflammatory mediators (e.g., cytokines) and activation of microglia and astrocytes could be responsible for the structural, functional, and molecular neuroplasticity changes observed in supraspinal structures, associated with pathological pain [ 123 ]. Bilateral increases in the density of microglia are observed in the infralimbic cortex of rats 7 days post-injury, without any detectable change in the other investigated regions, namely the ACC, prelimbic, and agranular insular cortices [ 124 ].…”
Section: Changes In the Pfc During Acute Painmentioning
confidence: 99%
“…Overall, despite the available data regarding neuroplastic changes in supraspinal structures associated with nervous system injury-induced pathological pain (Boadas-Vaello et al, 2017 ), the cellular and molecular processes occurring in these structures as a consequence of PNI are not yet fully understood. Particularly, since distinct subregions of PAG may play different or specific roles in the descending modulation of pain (McMullan and Lumb, 2006 ; Eidson and Murphy, 2013 ), it is of interest to investigate whether dlPAG and vlPAG show different pathophysiological responses after PNI, and whether these responses appear in parallel with RVM glial activation, and to do so in distinct PNI models.…”
Section: Introductionmentioning
confidence: 99%